Mn2+ doped AgInS2 photocatalyst for formaldehyde degradation and hydrogen production from water splitting by carbon tube enhancement. (October 2022) - Gu, Xinyue; Tan, Chen; He, Lixian; Guo, Jie; Zhao, Xia; Qi, Kezhen; Yan, Ya
Abstract: In this work, AgInS2 and Mn 2+ doped AgInS2 (Mn–AgInS2 ) with different Mn 2+ : (Ag + + In 3+ ) ratios were synthesized via a low temperature liquid method. The photocatalytic activity of the obtained samples was followed by taking formaldehyde as the target pollutant under visible light irradiation. The photocatalysts were passed through various characterization procedures to investigate their morphological, structural and photophysical characteristics. The optimal proportion sample [with the ratio n (Mn 2+ ): n (Ag + + In 3+ ) = 1:100] photodegraded about 79% formaldehyde in 150 min. These upgraded activities are attributed to the enhanced visible light absorption and superior charge separation due to the presence of Mn 2+ as confirmed site from charge separation measurements. In addition, a possible mechanism for the photodegradation of formaldehyde is proposed based on the experimental results. Furthermore, the photocatalytic water splitting performance of Mn–AgInS2 and multi-walled carbon nanotubes (MWCNTs) modified Mn–AgInS2 is investigated and compared under simulated sunlight irradiation, and remarkable hydrogen production is achieved (105 μmol h −1 g −1 ) by using the latter. Highlights: A low-temperature liquid method is used to prepare Mn 2+ doped AgInS2 . The photocatalytic performance of AgInS2 is improved by doping of Mn 2+ . High performance of the H2 production and formaldehyde removal over Mn–AgInS2 . The carbon nanotube modification promoted the separation efficiency of photogenerated carriers.